Rancang Bangun Heat Exchanger Tube Fin Tiga Pass Shell Satu Pass Untuk Mesin Pengering Empon-Empon - Setia Budi, Doni, Ir. Sartono Putro, MT (2017)
Heat Exchanger is device that facilitate the exchange of heat between two fluids that are at different temperatures while keeping them from mixing with each other. This research is aimed at fidding an influence of debt variety of Heat Exchanger tube fin single pass and shell triple pass for turmeric drainage. The debt of variety 0,026, 0,028, and 0,030 m3/s. Heat exchangers are used in this research has a cross flow., cold fluid such as air from the blower to flow into the heat exchanger, in the heat exhanger cold fluid will receive heat from hot fluid flowing in a shell that is pre-heated by the stove, and after that cold fluid is out of heat exchanger and into the engine medicinal dryer. The result of this research show that, if the cold fluid mass flow rate of air are bigger, it is means that temperature different, heat of cold fluid mass flow, ,overall heat transfer coefficient,heat transfer coefficient of cold fluid, efficiency and mass different of turmeric rate is bigger.